1994
DOI: 10.1126/science.7939721
|View full text |Cite
|
Sign up to set email alerts
|

PHAS-I as a Link Between Mitogen-Activated Protein Kinase and Translation Initiation

Abstract: PHAS-I is a heat-stable protein (relative molecular mass approximately 12,400) found in many tissues. It is rapidly phosphorylated in rat adipocytes incubated with insulin or growth factors. Nonphosphorylated PHAS-I bound to initiation factor 4E (eIF-4E) and inhibited protein synthesis. Serine-64 in PHAS-I was rapidly phosphorylated by mitogen-activated (MAP) kinase, the major insulin-stimulated PHAS-I kinase in adipocyte extracts. Results obtained with antibodies, immobilized PHAS-I, and a messenger RNA cap a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
553
3
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 641 publications
(588 citation statements)
references
References 19 publications
30
553
3
2
Order By: Relevance
“…In agreement with numerous previous studies (see for example, Lin et al, 1994;Graves et al, 1995;Gingras et al, 1996;Mendez et al, 1996), mouse and human 4E-BP1 were detected as multiple bands on gels in the vicinity of 20 kDa. These correspond to differentially phosphorylated forms, with hyperphosphorylated (g) 4E-BP1 migrating more slowly than the less phosphorylated (b and a) forms.…”
Section: Identification Of High-molecular-weight Forms Of 4e-bp1supporting
confidence: 93%
“…In agreement with numerous previous studies (see for example, Lin et al, 1994;Graves et al, 1995;Gingras et al, 1996;Mendez et al, 1996), mouse and human 4E-BP1 were detected as multiple bands on gels in the vicinity of 20 kDa. These correspond to differentially phosphorylated forms, with hyperphosphorylated (g) 4E-BP1 migrating more slowly than the less phosphorylated (b and a) forms.…”
Section: Identification Of High-molecular-weight Forms Of 4e-bp1supporting
confidence: 93%
“…These results suggest that Ang II activates p70 s6K through the pathway different from that of MAP kinases/p90 rsk. Recently it has been reported that MAP kinases phosphorylate PHAS-I, which is a heat-stable protein found in many tissues including the heart and the phosphorylated PHAS-I dissociates from translation initiation factor 4E, resulting in the initiation of translation [33]. Therefore, it is possible that the activations of both p70 s6K and MAP kinases are necessary for Ang II-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The 4E-binding proteins are reversibly phosphorylated in response to conditions which stimulate translation (Lin et al, 1994Lin and Lawrence, 1996;Fadden et al, 1997;Lawrence and Abraham, 1997) and this process favours Figure 4 Changes in levels of initiation factors in cycloheximide-treated BJAB cells. Exponentially growing cells were treated with cycloheximide (100 mg/ml) for the times indicated and cytoplasmic extracts prepared as described in Materials and methods.…”
Section: Is Inhibition Of Protein Synthesis Su Cient To Destabilize Ementioning
confidence: 99%